A Fantasy in Fashion: African American Empowerment in an Era of Opulence - Carter-David, Siobhan; Wu, Ellen (Race and Retail: Consumption across the Color Line, 2015)
Race has long shaped shopping experiences for many Americans. Retail exchanges and establishments have made headlines as flashpoints for conflict not only between blacks and whites, but also between whites, Mexicans, Asian Americans, and a wide variety of other ethnic groups, who have at times found themselves unwelcome at white-owned businesses.  Race and Retail documents the extent to which retail establishments, both past and present, have often catered to specific ethnic and racial groups. Using an interdisciplinary approach, the original essays collected here explore selling and buying practices of nonwhite populations around the world and the barriers that shape these habits, such as racial discrimination, food deserts, and gentrification. The contributors highlight more contemporary issues by raising questions about how race informs business owners’ ideas about consumer demand, resulting in substandard quality and higher prices for minorities than in predominantly white neighborhoods.  In a wide-ranging exploration of the subject, they also address revitalization and gentrification in South Korean and Latino neighborhoods in California, Arab and Turkish coffeehouses and hookah lounges in South Paterson, New Jersey, and tourist capoeira consumption in Brazil.   Race and Retail illuminates the complex play of forces at work in racialized retail markets and the everyday impact of those forces on minority consumers. The essays demonstrate how past practice remains in force in subtle and not-so-subtle ways.
Keywords: dept.his

An Academy at the Court of the Tsars: Greek Scholars and Jesuit Education in Early Modern Russia - Chrissidis, Nikolaos A. (NIU Press, 2015)
Keywords: 17th century; 17th century; Education, Higher; 17th century; Greeks; Education; History; History; Jesuits; Leichoudēs, Iōannikios, 1633-1717; Leichoudēs, Sōphronios, 1652-1730; Moskovskai︠a︡ slavi︠a︡no-greko-latinskai︠a︡ akademii︠a︡; Moscow; Russia; Russia (Federation); dept.his; faculty_collection

Our Land, Our Life, Our Future: Black South African Challenges to Territorial Segregation, 1913-1948 - Feinberg, Harvey M. (Hidden histories series, 2015)
Keywords: 1909-1961; History; History; South Africa; Land reform; Law and legislation; South Africa; dept.his; faculty_collection

Major Problems in American Indian History: Documents and Essays - Hurtado, Albert L.; Iverson, Peter; Bauer, William J.; Amerman, Stephen Kent (Major problems in American history series, 2015)
Keywords: History; History; Indians of North America; Indians of North America; Sources; dept.his; faculty_collection

Mapping and Charting in Early Modern England and France: Power, Patronage, and Production - Petto, Christine Marie (Toposophia, 2015)
Keywords: Cartography; England; France; History; History; Cartography; History; Map industry and trade; Paris; dept.his; faculty_collection

Vietnamese Traditional Medicine: A Social History - Thompson, Claudia Michele (History of medicine in Southeast Asia series, 2015)
Keywords: History; Medicine, Chinese; History; Vietnam; Medicine, Traditional; SCSU Faculty Scholar Award; Vietnam; award_winner; dept.his; faculty_collection; history; Medicine, Chinese Traditional; history; Smallpox; prevention & control; Traditional medicine

Greeks in seventeenth-century Russia - Chrissidis, N.A. (Portraits of Old Russia: Imagined Lives of Ordinary People, 1300-1745, 2015)
Keywords: dept.his

The World of Eastern Orthodoxy - Chrissidis, Nikolaos A. (The Oxford Handbook of Early Modern European History, 1350-1750, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Keywords: dept.his